The Older, the More Forgiving? Characteristics of Forgiveness of Chinese Older Adults - Tao, Linjin; Zhu, Tingting; Min, Yanglu; Ji, Mingxia (Frontiers in Psychology, 2021)
This study explores the characteristics of forgiveness in the aging cohorts, which is regarded to be associated with healthy outcomes. Data were drawn from a sample of 308 older adults (aged from 60 to 98 years) who completed the forgiveness questionnaire: forgiving others of The Heartland Forgiveness Scale (HFS) to examine explicit forgiveness, and among the participants, 44 older adults were administrated on the variant single category of implicit association test (SC-IAT) to examine the implicit forgiveness. The results revealed that (1) there is no correlation between explicit forgiveness and implicit forgiveness of older adults. (2) The result of explicit forgiveness is relatively high while that of implicit forgiveness is relatively low. (3) There was no significant correlation between explicit forgiveness and age, but there was significant difference between age groups, as forgiveness tendency of the elderly had a trough in the age group of 70–79 and then rebounded. (4) Implicit forgiveness was significantly correlated with age, and the difference between age groups was marginal. The forgiveness tendency of the elderly over 80 years old was significantly higher than that of the other two age groups. (5) Gender differences are found in both explicit and implicit forgiveness. The findings indicated that (1) explicit and implicit measures in this study have assessed independent and complementary aspects of forgiveness tendency in older adults. (2) Implicit forgiveness falls behind explicit forgiveness, and true internal forgiveness is difficult and rare in older adults according to data analysis. (3) The trend of explicit forgiveness with age is not obvious, because explicit forgiveness in the middle old age group presents an inflection point. However, implicit forgiveness increases slowly with age. (4) Women excel men in scores obtained with both explicit and implicit measures for forgiveness.